Human skeletal muscle xenograft as a new preclinical model for muscle disorders - Zhang, Yuanfan (Oxford University Press, 2014)
Development of novel therapeutics requires good animal models of disease. Disorders for which good animal models do not exist have very few drugs in development or clinical trial. Even where there are accepted, albeit imperfect models, the leap from promising preclinical drug results to positive clinical trials commonly fails, including in disorders of skeletal muscle. The main alternative model for early drug development, tissue culture, lacks both the architecture and, usually, the metabolic fidelity of the normal tissue in vivo. Herein, we demonstrate the feasibility and validity of human to mouse xenografts as a preclinical model of myopathy. Human skeletal muscle biopsies transplanted into the anterior tibial compartment of the hindlimbs of NOD-Rag1(null) IL2rγ(null) immunodeficient host mice regenerate new vascularized and innervated myofibers from human myogenic precursor cells. The grafts exhibit contractile and calcium release behavior, characteristic of functional muscle tissue. The validity of the human graft as a model of facioscapulohumeral muscular dystrophy is demonstrated in disease biomarker studies, showing that gene expression profiles of xenografts mirror those of the fresh donor biopsies. These findings illustrate the value of a new experimental model of muscle disease, the human muscle xenograft in mice, as a feasible and valid preclinical tool to better investigate the pathogenesis of human genetic myopathies and to more accurately predict their response to novel therapeutics.